Psychological Autopsy-A Review - Vasudeva Murthy C R (Al Ameen Medical College, 2010)
The psychological autopsy is thought to be the cornerstone of suicide research, providing more detailed knowledge than other methods. Its prime objective is to retrieve comprehensive information about suicide. Information is collected from key informants, available medical records and personnel and it consists of reconstructing the life style and personality of deceased along with details of circumstances, behaviors and events that led to the death of that individual.